2019
DOI: 10.1080/21580103.2019.1592787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of degraded land rehabilitation on carbon stocks and biodiversity in semi-arid region of Northern Ethiopia

Abstract: This study evaluated the effects of exclsoures (EXs) on restoring woody species diversity and carbon stocks over the adjacent degraded open grazing land (DOGL). Two proximate sites were purposively selected. Then, systematic sampling method was employed. A total of sixty plots were surveyed for both tree/shrub inventory and soil sampling purposes. Overall, 49 woody species belonging to 45 genera and 28 families were identified, it comprising 46 woody species in the EX and 26 woody species in the DOGL. Species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 45 publications
8
27
0
Order By: Relevance
“…The study indigenous AF practice declared that SOC stock increases with increasing species richness and Shannon diversity index. This is also line with the general trend that ecosystem with high biodiversity sequester more carbon in the soil than those which have lower diversity [54], [47] showed that SOC stock positive and significantly correlated with the species richness and [55] found that species richness correlated to SOC in homegarden of Kerala, India. However, the results of our study were in contrast to [53]found a negative relationship between SOC stock (depth = 0-60cm) and woody species diversity (i.e, Species richness and Shannon diversity index).…”
Section: Carbon Stocksupporting
confidence: 86%
See 1 more Smart Citation
“…The study indigenous AF practice declared that SOC stock increases with increasing species richness and Shannon diversity index. This is also line with the general trend that ecosystem with high biodiversity sequester more carbon in the soil than those which have lower diversity [54], [47] showed that SOC stock positive and significantly correlated with the species richness and [55] found that species richness correlated to SOC in homegarden of Kerala, India. However, the results of our study were in contrast to [53]found a negative relationship between SOC stock (depth = 0-60cm) and woody species diversity (i.e, Species richness and Shannon diversity index).…”
Section: Carbon Stocksupporting
confidence: 86%
“…for boundary planting AF practices. The SOC stock to biomass C ratio in AF practices is affected by several factors including age of the AF system that has been being practiced [49], types of tree species included and rotation age [12,36], soil type [50], elevation, climatic condition [51], silvicultural management and land-use history [47,52].…”
Section: Carbon Stockmentioning
confidence: 99%
“…The stand basal area at three EXs ranges of 3.1 -7.23 m 2 ha -1 . Similar results were reported from farm exclosure in Tigray, Northern Ethiopia [25] and in semi-arid region of Northern Ethiopia [26]. The total basal area for the three EXs are far less than that within the reported range for dry forests of Ethiopia (e.g.…”
Section: Species Composition and Species Diversitysupporting
confidence: 81%
“…Approximately 41% of global territory and 44% of cultivated land is dryland (Millennium Ecosystem Assessment 2005). While the semi-arid drylands are increasing triggered by human activities, combating land desertification to secure land productivity is important (Manaye et al 2019). The effects of desertification are the degradation of ecosystems, adverse effects on human health such as respiratory problems, and a reduction in cropland, leading to food availability issues.…”
Section: Introductionmentioning
confidence: 99%